Clinical Psychologists’ Experiences of Accessing Personal Therapy during Training: A Narrative Analysis - Wilson, Hannah May Ngaori; Weatherhead, Stephen; Davies, Jenny S (International Journal of Practice-based Learning in Health and Social Care, 2015)
The objectives of this study were to explore the experiences of trainee clinical psychologists who utilised therapy whilst training, and its role in their personal and professional development. Ten clinical psychologists were recruited, and asked to share their story of accessing personal therapy during training. Data were analysed using narrative analysis, which led to the development of four chapters: Chapter one explores the context of being a trainee clinical psychologist whilst experiencing therapy, including stressors encountered during training. In chapter two, participants discuss the stigma they felt in accessing personal therapy. Through chapter three, participants describe the journey of therapy itself, including difficult emotions they experienced and events such as ‘the ending’. Finally, chapter four details the personal and professional impact of their therapy journey. It is concluded that personal therapy can provide both personal and professional support to trainee clinical psychologists. However, some barriers may affect individuals seeking such support. The clinical and professional implications of these findings are discussed, in addition to recommendations for future research